ANALISIS PEMASARAN KAKAO DI DESA OMU KECAMATAN GUMBASA KABUPATEN SIGI (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Cacao (Theobroma cacao L) is a type of plantation that is often found in the Central Sulawesi Region. One area that can produce cocoa is Sigi Regency, there are 15 districts that can produce cocoa production in Sigi Regency. The purpose of this study was to determine the form of marketing channels, marketing margins, the share of prices received by farmers (producers) of cocoa and the efficiency of cocoa marketing in each channel in Omu Village, Gumbasa District, Sigi Regency. The results of the analysis show that there are two forms of marketing channels in Omu Village, Gumbasa Subdistrict, Sigi Regency, namely: Channel I) producers sell cocoa to collectors, then sell it to large traders and sell it again to end consumers (Brown House Industry). Channel II) Manufacturers sell cocoa to large traders, then wholesalers sell to end consumers. The total marketing margin of cocoa obtained in the first channel is Rp. 5,500, and the total margin obtained in the second channel is Rp.3,000. The share of prices received by producers in channel I was 82.53% while the share of prices received by producers in channel II was 90.47%. Marketing efficiency of channel I was 2.06%, and channel II was 1.82%, so channel II was more efficient than channel I.
Keywords: Consumer; efficiency; margin